Implantation of In Vitro Tissue Engineered Muscle Repair Constructs and Bladder Acellular Matrices Partially Restore In Vivo Skeletal Muscle Function in a Rat Model of Volumetric Muscle Loss Injury - Corona, Benjamin T. (Tissue Eng Part A, 2014)
The frank loss of a large volume of skeletal muscle (i.e., volumetric muscle loss [VML]) can lead to functional debilitation and presents a significant problem to civilian and military medicine. Current clinical treatment for VML involves the use of free muscle flaps and physical rehabilitation; however, neither are effective in promoting regeneration of skeletal muscle to replace the tissue that was lost. Toward this end, skeletal muscle tissue engineering therapies have recently shown great promise in offering an unprecedented treatment option for VML. In the current study, we further extend our recent progress (Machingal et al., 2011, Tissue Eng; Corona et al., 2012, Tissue Eng) in the development of tissue engineered muscle repair (TEMR) constructs (i.e., muscle-derived cells [MDCs] seeded on a bladder acellular matrix (BAM) preconditioned with uniaxial mechanical strain) for the treatment of VML. TEMR constructs were implanted into a VML defect in a tibialis anterior (TA) muscle of Lewis rats and observed up to 12 weeks postinjury. The salient findings of the study were (1) TEMR constructs exhibited a highly variable capacity to restore in vivo function of injured TA muscles, wherein TEMR-positive responders (n=6) promoted an ≈61% improvement, but negative responders (n=7) resulted in no improvement compared to nonrepaired controls, (2) TEMR-positive and -negative responders exhibited differential immune responses that may underlie these variant responses, (3) BAM scaffolds (n=7) without cells promoted an ≈26% functional improvement compared to uninjured muscles, (4) TEMR-positive responders promoted muscle fiber regeneration within the initial defect area, while BAM scaffolds did so only sparingly. These findings indicate that TEMR constructs can improve the in vivo functional capacity of the injured musculature at least, in part, by promoting generation of functional skeletal muscle fibers. In short, the degree of functional recovery observed following TEMR implantation (BAM+MDCs) was 2.3×-fold greater than that observed following implantation of BAM alone. As such, this finding further underscores the potential benefits of including a cellular component in the tissue engineering strategy for VML injury.